Is movie success a judgment device? When more is not better. Issue 12 (17th October 2018) - Addis, Michela; Holbrook, Morris B.
Abstract: The purpose of this study is to investigate the relative impact, if any, of three main aspects of movie success (Simonton, 2009)—namely, reviewers' ratings, opening box office, and Oscar nominations—as market cues that might influence consumers' subsequent evaluative assessments. Based on public real‐world data, via path analysis on longitudinal observations for motion pictures released in two different years, Studies 1 and 2 test and compare the impacts of these key success criteria and their interactions. Measures of the relevant variables were gathered over time and statistically controlled for typical objective movie features available in the market at the beginning of any motion‐picture life cycle. Findings show that only reviewers' ratings have an impact on consumers' quality judgments, whereas opening box office and Oscar nominations have neither a main nor an interaction effect. Thus, they do not act as judgment devices.